2020
DOI: 10.1155/2020/6912015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Huoxiang Zhengqi Pill on Early Neurological Deterioration in Patients with Acute Ischemic Stroke Undergoing Recanalization Therapy and Predictive Effect of Essen Score

Abstract: Early neurologic deterioration (END) in the acute phase of ischemic stroke is a serious clinical event, which is closely related to poor prognosis. Therefore, it is important to identify presentation features that predict END and take relevant treatment measures, as they could help to prevent the deterioration of high-risk patients. The prospective intervention study was carried out from January 2018 to December 2019. We included consecutive patients hospitalized for acute ischemic stroke (AIS) within 6 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…16 In the TOPCAT trial, the incidence of any stroke was 1.02 per 100 patient-years in patients with HFpEF. Previous studies have demonstrated the discriminatory ability of the ESRS on early neurologic deterioration, 17 MI, 6 or the combined vascular events including stroke, MI, or death in patients with TIA/stroke, 7 and carotid atherosclerosis in Chinese general populations. 18 The discriminatory performance of the ESRS is not always satisfactory in all the enrolled populations.…”
Section: Discussionmentioning
confidence: 99%
“…16 In the TOPCAT trial, the incidence of any stroke was 1.02 per 100 patient-years in patients with HFpEF. Previous studies have demonstrated the discriminatory ability of the ESRS on early neurologic deterioration, 17 MI, 6 or the combined vascular events including stroke, MI, or death in patients with TIA/stroke, 7 and carotid atherosclerosis in Chinese general populations. 18 The discriminatory performance of the ESRS is not always satisfactory in all the enrolled populations.…”
Section: Discussionmentioning
confidence: 99%